Molecular and particle modelling of laminar and turbulent flows - Greenspan, Donald (World Scientific, 2005)
Turbulence is the most fundamental and, simultaneously, the mostcomplex form of fluid flow. However, because an understanding ofturbulence requires an understanding of laminar flow, both areexplored in this book. Groundwork is laid by careful delineation of the necessary physical, mathematical, and numerical requirements for the studies which follow, and include discussions of N-body problems, classical molecularmechanics, dynamical equations, and the leap frog formulas for verylarge systems of second order ordinary differential equations.